Steps To Write Good Research: A Summary From The Book "Al-Murşid Fi Kitaba Al-Abhaś" By Helmy Mohamed Fouda - Makhisoh, Iis (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2022)
Writing research or reports are two necessary processes when studying, especially for university students. Most of these students had never managed to write research or reports, were not used to frequenting modern libraries, and were not used to using them. Some educational institutions used to hold seminars in which new students learn about ways to use the library and how to write research or reports. Helmy Muhammad Fouda believed that writing down the results of these seminars in one book is necessary to guide students to a proper way to carry out the process of using the library and how to write good research or reports. The aforementioned book consists of five chapters that talk about (1) the nature of research and reports; (2) the role of the library in writing them; (3) research sources; (4) disclosure of sources and methods of their use; And the last (5) writing the research. But this article concentrates on three issues only, which are (1) the nature of research and reports; (2) the role of the library; and (3) research writing.